The Legislative Performance of the Kurdistan-Iraq Parliament for the Second and Third Sessions (a comparative study) - Yas, Rashid Emara; Mohamad, Ayub Mohamad Taeeb (Journal of Legal and Political Studies, 2018)
"In order to know the performance and effectiveness of any parliament, before everything, it is necessary to know the level of legislative performance and activities of this institution, this is because legislation and making laws are a key function and the main role of the parliament, and directly related to the organizing of the society and the administration of the state in general. The summary of this research is to study and argue the legislative performance of the Iraqi Kurdistan Parliament for the second and third rounds, as well as evaluating and comparing the level of performance and effectiveness of the Parliament for these rounds, this is based on some criteria and scientific indicators in which parliamentary studies based on in the world, these indicators are identified by the Inter-Parliamentary Union (IPU) to evaluate the effectiveness of the parliament. Despite the similarity in the level of legislative performance of the Iraqi Kurdistan Parliament and its achievements in this area for the second and third rounds, but at the same time there are some differences between these rounds particularly in the area of legislative performance, laws of budget, the number of bills submitted by the committees of the Parliament along with the draft laws submitted by the government and the number of meetings of Parliament, as well as the way of discussion of projects and other issues related to the legislative performance. Therefore, It can be said that the Iraqi Kurdistan Parliament has tried to be effective in its legislative performance during these rounds, but it has faced some barriers due to the existence of some weakness and failure in some areas of legislative performance. In order to enhance its performance in this areas, the Parliament of Kurdistan must solve these obstacles which have faced. "
Keywords: Parliament; Legislative Performance; Kurdistan regine; Iraq; Kurdistan Parliament